Dispatches From New York: The Travels of a Moroccan diplomat at the end of the age of empire. Issue 3 (4th May 2023) - Stenner, David
ABSTRACT: The Moroccan nationalist Mehdi Bennouna traveled to New York in 1947 to advocate for his country's independence before the United Nations. Throughout his six-month stay, he wrote daily reports to inform his colleagues back home about his activities, focusing not only on politics but also detailing the rhythm of daily life in the global metropolis. He thereby reasserted Morocco's rightful place on the global stage and portrayed the kingdom's urban bourgeoisie as the social force most capable of leading the nation into the future. In many ways, his diary contained resonances of the rihla account penned by the Moroccan diplomat Mohammad al-Saffar, who had provided a detailed report about life under industrial modernity upon his return from France in 1845. Contrasting the two travelogues offers unique a window onto the transformation Moroccan society during a century of European colonial expansion and contraction. The same international system, which had once posed an eminent threat to the kingdom's sovereignty, now seemed to invite Morocco's return on the basis of true equality.